Hubungan Dukungan Keluarga terhadap Perencanaan Karir Siswa di SMA Negeri 2 Sungai Selan - Safitri, Dina (IJoCE: Indonesian Journal of Counseling and Education, 2025)
This study discusses the relationship between family support and students’ career planning at SMA Negeri 2 Sungai Selan. The problem raised is the low level of students’ career planning which is thought to be influenced by parental support. The approach used is quantitative research with a correlation method, involving 30 students of class XII MIPA 1 as a sample. Data were collected through questionnaires that have been tested for validity and reliability. The results of the analysis show a positive and significant relationship between family support and students’ career planning, with a correlation value of 0.788. The conclusion of this study confirms that family support plays an important role in improving students’ career planning, so it is recommended that parents be more active in providing support and guidance to their children in planning their future careers.